ISU GLOBAL WARMING DAN SIKAP DUNIA INTERNASIONAL - Pratiwi, Diah Ayu (JURNAL DIMENSI, 2013)
The issue of global warming discourse and international attention today. It is characterized by proliferation and increasingly intense international conferences that discuss the issue. This article aims to analyze and identify the issue of global warming as an issue of non-conventional and knowing how the international attitude towards the issue and where the direction of policy foreign countries tackle the issue of global warming. This paper uses descriptive qualitative research methods. From this article we concluded the current attitude of the international community concerned about the issue of global warming. Broadly speaking, the international negotiations on global warming and climate change involves two main camps, which developed countries (industrialized countries) and developing countries. Although sometimes stagnated, international conference on global warming and climate change continue to be done by the countries in the world to achieve a win-win solution. It is solely in order to achieve the basic objective, namely the achievement of prosperity and peace the real world.